Structure and dynamics of benzyl-NX3 (X = Me, Et) trifluoromethanesulfonate ionic liquids - Sunda, Anurag Prakash; Dhavale, Vishal M.; Kurungot, Sreekumar; Venkatnathan, Arun (Journal of Physical Chemistry B, 2014)
Ammonium-based benzyl-NX3 (X = methyl, ethyl) trifluoromethanesulfonate (TFA) ionic liquids (ILs) are low cost, nontoxic, thermally stable ion-conducting electrolytes in fuel cells and batteries. In the present study, we have characterized the structure and dynamics of these ILs using molecular dynamics (MD) simulations and ionic conductivity using electro-chemical impedance spectroscopy (EIS) at varying temperature and relative humidity (RH). Results from MD simulations predict that cation-cation and cation-anion interactions are stronger in benzyltrimethylammonium (BzTMA) compared to benzyltriethylammonium (BzTEA) that diminish with increase in RH. Further, the BzTMA cations show both C-H/Ph (center of mass of phenyl ring) and cation-Ph interactions whereas BzTEA cations show only strong cation-Ph interactions. The C-H/Ph interactions (psi >= 90 degrees, d(H-Ph) <= 4 angstrom, theta < 50 degrees and d(C.Ph) <= 4.3 angstrom) in BzTMA cations increase with RH and are highest at RH = 90%. The cumulative impact of electrostatic, cation/Ph, and C-H/Ph interactions results in lower conductivity of BzTMA-TFA IL compared to BzTEA-TFA IL. The EIS measurements show that the trends in ionic conductivity of ILs at RH = 30 and 90% are qualitatively similar to the Nernst-Einstein conductivity from MD simulations. The ionic conductivity of BzTEA-TFA IL is similar to 3 times higher than BzTMA-TFA IL at 353 K and RH = 90%.

Synthesis of an efficient heteroatom-doped carbon electro-catalyst for oxygen reduction reaction by pyrolysis of protein-rich pulse flour cooked with SiO2 nanoparticles - Gokhale, Rohan; Unni, SreeKuttan M.; Puthusseri, Dhanya; Kurungot, Sreekumar; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2014)
Development of a highly durable, fuel-tolerant, metal-free electro-catalyst for oxygen reduction reaction (ORR) is essential for robust and cost-effective Anion Exchange Membrane Fuel Cells (AEMFCs). Herein, we report the development of a nitrogen-doped (N-doped) hierarchically porous carbon-based efficient ORR electrocatalyst from protein-rich pulses. The process involves 3D silica nanoparticle templating of the pulse flour(s) followed by their double pyrolysis. The detailed experiments are performed on gram flour (derived from chickpeas) without any in situ/ex situ addition of dopants. The N-doped porous carbon thus generated shows remarkable electrocatalytic activity towards ORR in the alkaline medium. The oxygen reduction on this material follows the desired 4-electron transfer mechanism involving the direct reduction pathway. Additionally, the synthesized carbon catalyst also exhibits good electrochemical stability and fuel tolerance. The results are also obtained and compared with the case of soybean flour having higher nitrogen content to highlight the significance of different parameters in the ORR catalyst performance.

Surface-modified single wall carbon nanohorn as an effective electrocatalyst for platinum-free fuel cell cathodes - Unni, SreeKuttan M.; Ramadas, Sarath; Illathvalappil, Rajith; Bhange, Siddheshwar N.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2015)
Platinum (Pt) and its alloys are routinely used in the cathodes of polymer electrolyte membrane fuel cells (PEMFCs) due to their high electrocatalytic activity in oxygen reduction reactions (ORRs). A variety of alternative materials have been examined as alternatives to Pt, but most of these had low activity and their performance deteriorated even further in use. In the present study an alternate electrocatalyst has been examined, obtained by a simple surface modification of single-walled carbon nanohorns by simultaneous doping with Fe and N at 900 degrees C (FeNCNH-900). This had an ORR activity superior to that of 40 wt% Pt on carbon (Pt/C). Compared to Pt/C, FeNCNH-900 gave a 30 mV improvement in onset potential and a 20 mV gain in half-wave potential in an ORR. Its high activity is the result of the simultaneous modulation achieved by the high surface area and the microporosity of carbon nanohorns, together with the establishment of the desired nitrogen-iron coordinated pyrrolic active centres. The catalyst showed excellent electrochemical stability and, most notably, its ORR activity was still increasing after 1000 cycles. Single-cell fuel cell performance using FeNCNH-900 as cathode catalyst showed a maximum power density of 35 mW cm(-2) under alkaline conditions.

Surface-tuned Co3O4 nanoparticles dispersed on nitrogen-doped graphene as an efficient cathode electrocatalyst for mechanical rechargeable zinc-air battery application - Singh, Santosh K.; Dhavale, Vishal M.; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2015)
The most vital component of the fuel cells and metal air batteries is the electrocatalyst, which can facilitate the oxygen reduction reaction (ORR) at a significantly reduced overpotential. The present work deals with the development of surface-tuned cobalt oxide (Co3O4) nanoparticles dispersed on nitrogen-doped graphene as a potential ORR electrocatalyst possessing some unique advantages. The thermally reduced nitrogen-doped graphene (NGr) was decorated with three different morphologies of Co3O4 nanoparticles, viz., cubic, blunt edged cubic, and spherical, by using a simple hydrothermal method. We found that the spherical Co3O4 nanoparticle supported NGr catalyst (Co3O4-SP/NGr-24h) has acquired a significant activity makeover to display the ORR activity closely matching with the state-of-the-art Pt supported carbon (PtC) catalyst in alkaline medium. Subsequently, the Co3O4-SP/NGr-24h catalyst has been utilized as the air electrode in a Zn-air battery, which was found to show comparable performance to the system derived from PtC. Co3O4-SP/NGr-24h catalyst has shown several hours of flat discharge profile at the discharge rates of 10, 20, and 50 mA/cm(2) with a specific capacity and energy density of similar to 590 mAh/g(-zn) and,840 Wh/kg(-zn), respectively, in the primary Zn-air battery system. In conjunction, Co3O4-SP/NGr-24h has outperformed as an air electrode in mechanical rechargeable Zn-air battery as well, which has shown consistent flat discharge profile with minimal voltage loss at a discharge rate of 50 mA/cm(2). The present results, thus demonstrate that the proper combination of the tuned morphology of Co3O4 with NGr will be a promising and inexpensive material for efficient and ecofriendly cathodes for Zn-air batteries.
Keywords: electrocatalyst; mixed facets; oxygen reduction reaction; rechargeable zinc-air battery; surface morphology

Switching closed-shell to open-shell phenalenyl: toward designing electroactive materials - Pariyar, Anand; Vijaykumar, Gonela; Bhunia, Mrinal; Dey, Suman Kr.; Singh, Santosh K.; Kurungot, Sreekumar; Mandal, Swadhin K. (Journal of the American Chemical Society, 2015)
Open-shell phenalenyl chemistry started more than half a century back, and the first solid-state phenalenyl radical was realized only 15 years ago highlighting the synthetic challenges associated in stabilizing carbon-based radical chemistry, though it has great promise as building blocks for molecular electronics and multifunctional materials. Alternatively; stable closed-shell phenalenyl has tremendous potential as it can be utilized, to create an in situ open-shell state by external spin injection. In the present study, we have designed a closed-shell phenalenyl-based iron(III) complex, Fe-III(PLY)(3) (PLY-H = 9-hydroxyphenalenone) displaying an excellent electrocatalytic property as cathode material for one compartment membraneless H2O2 fuel cell. The power density output Of Fe-III(PLY)(3) is nearly 15-fold higher than the structurally related model compound Fe-III(acac)(3) (acac = acetylacetonate) and nearly 140-fold higher than an earlier reported mononuclear Fe(III) complex; Fe-III(Pc)Cl (Pc = pthalocyaninate), highlighting the role of switchable closed-shell phenalenyl moiety for electron-transfer process in designing electroactive materials.

Strategic Preparation of Efficient and Durable NiCo Alloy Supported N-Doped Porous Graphene as an Oxygen Evolution Electrocatalyst: A Theoretical and Experimental Investigation - Singh, Santosh K.; Kumar, Deepak; Dhavale, Vishal M.; Pal, Sourav; Kurungot, Sreekumar (Advanced Materials Interfaces, 2016)
Development of an efficient and durable water splitting electrocatalyst holds a great commitment for the future energy devices. The real application of oxygen evolution reaction (OER) catalysts mainly suffers from sluggish kinetics and high overpotential except for the Ir and Ru-based systems. However, the high cost and vulnerability of the Ir and Ru metals are the main hostiles to use them for marketization. Herein, a high-performance OER electrocatalyst consisting of NiCo alloy nanoparticles supported on high surface area N-doped porous graphene (NiCo/pNGr(75: 25)) is reported. The importance of the doped-N for achieving the uniform dispersion-cum-effective interaction of the size controlled NiCo alloy nanoparticles has been explicitly investigated by transmission electron microscopy, X-ray diffraction, X-ray photo electron spectroscopy, Raman, density functional theory (DFT) calculations, etc. The electrochemical analysis of NiCo/pNGr(75: 25) shows an overpotential of approximate to 260 mV at 10 mA cm(-2) with a smaller Tafel slope of approximate to 87 mV dec(-1) and long catalytic durability. DFT calculations are done to check the interaction between the NiCo alloy nanoparticles and the defective sites of pNGr and also with the doped-N, which could be attained for maintaining long catalytic durability. Furthermore, NiCo/pNGr(75: 25) is used as an OER catalyst to fabricate an electrolyzer, which works at very low potential of 1.5 V in 1 M KOH.

Selective isolation and eradication of E. coli associated with urinary tract infections using anti-fimbrial modified magnetic reduced graphene oxide nanoheaters - Halouane, Fatima; Jijie, Roxana; Meziane, Dalila; Li, Chengnan; Singh, Santosh K.; Bouckaert, Julie; Jurazek, Jean; Kurungot, Sreekumar; Barras, Alexandre; Li, Musen; Boukherroub, Rabah; Szunerits, Sabine (Journal of Materials Chemistry B, 2017)
The fast and efficient elimination of pathogenic bacteria from water, food or biological samples such as blood remains a challenging task. Magnetic isolation of bacteria from complex media holds particular promise for water disinfection and other biotechnological applications employing bacteria. When it comes to infectious diseases such as urinary tract infections, the selective removal of the pathogenic species in complex media such as human serum is also of importance. This issue can only be accomplished by adding pathogen specific targeting sites onto the magnetic nanostructures. In this work, we investigate the potential of 2-nitrodopamine modified magnetic particles anchored on reduced graphene oxide (rGO) nanocomposites for rapid capture and efficient elimination of E. coli associated with urinary tract infections (UTIs) from water and serum samples. An optimized magnetic nanocarrier achieves a 99.9% capture efficiency even at E. coli concentrations of 1 x 10(1) cfu mL(-1) in 30 min. In addition, functionalization of the nanostructures with poly(ethylene glycol) modified pyrene units and anti-fimbrial E. coli antibodies allowed specific elimination of E. coli UTI89 from serum samples. Irradiation of the E. coli loaded nanocomposite with a near-infrared laser results in the total ablation of the captured pathogens. This method can be flexibly modified for any other pathogenic bacteria, depending on the antibodies used, and might be an interesting alternative material for a magnetic-based body fluid purification approach.

Single cell fabrication towards the realistic evaluation of a CNT-strung ZIF-derived electrocatalyst as a cathode material in alkaline fuel cells and metal-air batteries - Aiyappa, Harshitha Barike; Bhange, Siddheshwar N.; Sivasankaran, Vijitha P.; Kurungot, Sreekumar (ChemElectroChem, 2017)
The development of an electrocatalyst possessing all the vital requisites of an ideal electrode material, such as high porosity, high conductivity, and high intrinsic electrochemical activity, holds a decisive key in determining the activity of the triplephase boundary in many energy devices like fuel cells and metal-air battery systems. In the present work, highly porous cobalt-based ZIFs are strung along the highly conducive CNT backbone by using a simple one-pot technique at room temperature, which is then utilized to derive a porous, corrosion-resistant, Co nanoparticle-embedded electrocatalyst. Herein, for the first time, the single cell performance of the Co-ZIF-67-derived electrocatalyst has been evaluated by fabricating membrane electrode assemblies of alkaline exchange membrane fuel cell (AEMFC) and zinc-air battery (ZAB) systems. A maximum power density of 296 mW/cm(2) (vs. 317 mW/cm(2) for 40 wt.% Pt/C) and 60 mW/cm(2) (vs. 64 mW/cm(2) for 40 wt.% Pt/C) in the single cells of ZAB and AEMFC systems, respectively, establishes the practical proficiency of the homemade electrocatalyst for cathode applications during realistic system-level validations.
Keywords: Batteries; Carbon nanotubes; Composite materials; fuel cells; metal-organic frameworks

Sensitive electrochemical detection of cardiac troponin I in serum and saliva by nitrogen-doped porous reduced graphene oxide electrode - Chekin, Fereshteh; Vasilescu, Alina; Jijie, Roxana; Singh, Santosh K.; Kurungot, Sreekumar; Iancu, Madalina; Badea, Gabriela; Boukherroub, Rabah; Szunerits, Sabine (Sensors and Actuators B-Chemical, 2018)
Cardiovascular diseases pose one of the highest mortality risks among all diseases in developed countries, steadily increasing the burden on the health systems. Early diagnosis of cardiovascular diseases has consequently become highly important to decrease mortality and to use more adapted therapeutic decisions. We demonstrate here the utility of nitrogen-doped reduced graphene oxide (N-prGO) for detecting and quantifying of cardiac troponin I (cTnI), a key human cardiac protein biomarker, under physiologically relevant conditions. Non-covalent modification of N-prGO by 1-pyrenecarboxylic acid (py-COOH) and poly(ethylene glycol) modified pyrene (py-PEG) ligands allowed the covalent integration of Tro4 aptamer, known for its high selectivity towards cTnI. Using differential pulse voltammetry (DPV), a label-free electrochemical sensor for cTnI for concentrations down to 1 pgmL(-1) in human serum could be obtained. This sensitive detection arises from the integration of a porous nanomaterial with excellent electrochemical properties being easily amendable to site-specific surface modification. (C) 2018 Elsevier B.V. All rights reserved.

Superprotonic conductivity in flexible porous covalent organic framework membranes - Banerjee, Rahul; Sasmal, Himadri Sekhar; Harshitha, B. A.; Bhange, Siddheshwar; Karak, Suvendu; Halder, Arjun; Kurungot, Sreekumar (Angewandte Chemie, 2018)
Poor mechanical stability of the polymer electrolyte membranes (PEMs) remains one of the bottlenecks towards improving the performance of the proton exchange membrane (PEM) fuel cells. The present work proposes a unique way to utilize crystalline covalent organic frameworks (COFs) as a self‐standing, highly flexible membrane to further boost the mechanical stability of the material without compromising its innate structural characteristics. The as‐synthesized p‐toluene sulfonic acid loaded covalent organic framework membranes (COFMs) showing the highest proton conductivity amongst all crystalline porous organic polymeric materials reported till date, as high as 7.8 x 10‐2 S cm‐1, have been further tested under real PEM operating conditions to ascertain their practical utilization as proton exchange membranes. Attainment of 24 mW cm‐2 power density, which is the highest among COFs and MOFs, highlights the possibilityof using a COF membrane over the other state‐of‐the‐art crystalline porous polymeric materials reported to date.

Studies on nano composites of SPEEK/ethylene glycol/cellulose nanocrystals as promising proton exchange membranes - Bano, Saleheen; Negi, Yuvraj S.; Illathvalappil, Rajith; Kurungot, Sreekumar; Ramya, K. (Electrochimica Acta, 2019)
The present work deals with fabrication and characterisations of nano-composite membranes composed of sulfonated poly (ether ether ketone) (SPEEK) cross-linked and reinforced with ethylene glycol (EG) and cellulose nanocrystals (CNCs) respectively. The thin films of cross-linked composite membranes were prepared by solvent casting method and further analysed for physicochemical and electrochemical properties to execute their applicability as promising proton exchange membrane (PEM) in fuel cells. The process of cross-linking helps to improve the strength and dimensional stability of bare SPEEK membranes without compromising with conductivity. However, presence of CNCs further improves the strength and provides an effective pathway for the conduction of protons in membranes by interacting through their surface hydroxyl and sulfonic acid groups with ionic moieties of polymer matrix. All prepared composite membranes showed good oxidative and thermal stability along with good proton conductivity. The cross-linked SPEEK membranes with 4 wt% loading of CNCs possess an appreciable proton conductivity of 0.186 S/cm at 95 degrees C and 95% RH which is comparable to Nafion 117. From the view point of above studies, the prepared nano-composite can be described as promising proton exchange membrane for fuel cells. (c) 2018 Elsevier Ltd. All rights reserved.
Keywords: Cellulose nanocrystals; Cross-linked SPEEK; fuel cell; oxidative stability; proton conductivity

Synthesis of ultrathin PEDOT on carbon nanotubes and shear thinning xanthan Gum-H2SO4 gel electrolyte for supercapacitors - Soni, Roby; Bhange, Siddheshwar N.; Athira, E.; Chetry, Rashmi; Kurungot, Sreekumar (ChemElectroChem, 2019)
Resistance of the electrode material play a vital role for applications in supercapacitors, where lowering the resistance leads to improved performance. Poly(3,4-ethylene dioxythiophene) (PEDOT) possesses high theoretical conductivity; however, the high density of grain boundaries, low accessible surface area, and low rate capability have been pervasive issues affecting the PEDOT-based supercapacitors. To this end, a hydrothermal method is proposed in this work where oxygen functional groups incorporated on the surface of carbon nanotubes (CNTs) are utilized to polymerize 3,4-ethylenedioxythiophene (EDOT). PEDOT forms an ultrathin, well-aligned coating on the surface of CNTs. This arrangement minimizes the number of grain boundaries and increases the electrochemically active surface area. Additionally, a shear-thinning Xanthan gum-H2SO4 gel electrolyte is introduced to overcome the low impregnation of the conventional polyvinyl-based electrolyte due to the hydrophobicity of the CNT-PEDOT composite. A supercapacitor based on this material showed a very low Equivalent Series Resistance (ESR) of 0.31 which leads to a high power density of 74 W cm(-3).
Keywords: gel electrolyte; PEDOT; shear thinning; supercapacitor; xanthan gum

Scalable synthesis of manganese-doped hydrated vanadium oxide as a cathode material for aqueous zinc-metal battery - Ghosh, Meena; Dilwale, Swati; Vijayakumar, Vidyanand; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2020)
Rechargeable aqueous zinc-metal batteries (ZMBs) are considered as potential energy storage devices for stationary applications. Despite the significant developments in recent years, the performance of ZMBs is still limited due to the lack of advanced cathode materials delivering high capacity and long cycle life. In this work, we report a low-temperature and scalable synthesis method following a surfactant-assisted route for preparing manganese-doped hydrated vanadium oxide (MnHVO-30) and its application as the cathode material for ZMB. The as-prepared material possesses a porous architecture and expanded interlayer spacing. Therefore, the MnHVO-30 cathode offers fast and reversible insertion of Zn2+ ions during the charge/discharge process and delivers 341 mAh g(-1) capacity at 0.1 A g(-1). Moreover, the MnHVO-30 parallel to Zn cell retains 82% of its initial capacity over 1200 stability cycles, which is higher compared to that of the undoped system. Besides, a quasi-solid-state home-made pouch cell with an area of 3.3 x 1.6 cm(2) and 3.6 mg cm(-2) loading is assembled, achieving 115 mAh g(-1) capacity over 100 stability cycles. Therefore, this work provides an easy and attractive way for preparing efficient cathode materials for aqueous ZMBs.
Keywords: anionic surfactant; hydrated vanadium pentoxide; Nafion ionomer membrane; post-lithium battery; quasi-solid-state battery

Seed-mediated growth of Pt on high-index faceted Au nanocrystals: the ag lining and implications for electrocatalysis - Roy, Debashree; Rajendra, Ranguwar; Gangadharan, Pranav K.; Pandikassala, Ajmal; Kurungot, Sreekumar; Ballav, Nirmalya (ACS Applied Nano Materials, 2021)
Bimetallic Au@Pt nanocrystals (NCs) offer a unique combination of plasmonic and catalytic properties and are a growing field of research. Herein, we report an unusual observation in the behavior of silver ions (Ag+) which was found to play a dominant role in dictating the Pt deposition in a seed-mediated growth method. `While the literature is replete with various instances of Ag-assisted Pt deposition whereby higher concentration of Ag+ translates into a thicker Pt shell, in the present study, contradictory observations were made. In the presence of lower amounts of Ag+, thick Pt shells were visualized, while at higher concentrations of Ag+, the extent of Pt deposition via the galvanic replacement reaction was reduced. Additionally, the presence of Ag was deemed necessary for the Pt deposition to take place, either in the form of an underpotential deposition layer on the Au NCs or by introducing Ag+ in the growth solution. We have demonstrated our findings on two different Au NCs enclosed with high-index facets, concave cuboid, and elongated tetrahexahedra, which mirror similar observations and provide generality to our claim. To the best of our knowledge, the time required for Pt deposition on the Au core in the present work is the least among the reported seed-mediated routes. Furthermore, this work, besides presenting a facile and general route for the amalgamation of catalytic and plasmonic properties in hybrid Pt-Au NCs, sheds light on the mechanistic aspects of Ag-assisted wet-chemical generation of bimetallic Au@Pt NCs. The overall electrocatalytic performance of our Au@Pt NCs toward the oxygen reduction reaction was realized to be impressive.
Keywords: bimetallic nanostructure; galvanic replacement reaction; high-index facet; oxygen reduction reaction; seed-mediated growth; underpotential deposition

Sulfonated polyvinyl alcohol ionomer membrane favoring smooth electrodeposition of zinc for aqueous rechargeable zinc metal batteries - Vijayakumar, Vidyanand; Torris, Arun; Kurian, Maria; Mathew, Megha Mary; Ghosh, Meena; Khairnar, Ajay B.; Badiger, Manohar V.; Kurungot, Sreekumar (Sustainable Energy & Fuels, 2021)
One of the failure mechanisms of aqueous rechargeable zinc metal batteries (AZMBs) involves high surface area zinc (HSAZ)/dendrite-like deposits over the Zn-metal anode during long-term cycling. Negatively charged (anionic) polymeric ionomer electrolyte membranes and separators are known for suppressing the dendrite-/HSAZ-induced failure of AZMBs. However, the preparation of cost-effective and non-fluorinated ionomers from cheap and environmentally friendly polymers is essential to leverage the feasibility of AZMBs. The current work demonstrates the potential of an ionomer electrolyte membrane (P-AS-C-Zn) made by the crystallization-induced physical cross-linking of sulfonated poly (vinyl alcohol) (PVS) and poly (vinyl alcohol) (PVA) as a dendrite-/HSAZ-inhibiting separator for AZMBs. The P-AS-C-Zn membranes exhibited excellent Zn plating/stripping behavior with a stable voltage vs. time profile beyond 1100 h, compared to their neutral PVA-C-Zn counterpart without any ionomer character (cell failure at close to 280 h). Applying the optimized P-AS-C-Zn membrane in a MnO2||Zn full cell helps retain about 50% of the initial capacity close to 600 cycles in the absence of extra manganese salt in the electrolyte, which is indeed promising.

Synergistic effect of B site co-doping with Co and Ce in bifunctional oxygen electrocatalysis by oxygen deficient brownmillerite Ba2In2O5 - Thundiyil, Shibin; Kurungot, Sreekumar; Devi, R. Nandini (Catalysis Today, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Specificity in oxygen reduction and evolution reactions is pivotal in bifunctional catalysts in advanced energy devices which are expected to be active in a wide potential window and stable in both electrochemically reducing and oxidising atmospheres. State of the art noble metal catalysts for these reactions are fraught with issues whereas, metal oxides are expected to be stable in large potential window and can be tuned to have better bifunctional activity. Catalytically active metals, redox centres, oxygen vacancies etc. are some of the features of structured oxides which can be exploited in oxygen electrocatalysis. Brownmillerite family of compounds with general formula, A<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">B<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> has high concentrations of ordered oxygen vacancy in a layer and can be promising bifunctional oxygen electrocatalysts, by appropriate B site doping. Ba<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">In<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> is a well-studied system for its oxide ion conductivity and proximity of active B sites to O vacancies provide good O adsorption sites which are catalytically active. Here, cobalt and cerium are co-doped in Ba<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">In<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">2<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-size: 13.5px; line-height: 0; position: relative; bottom: -0.25em; color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">5<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">, anticipating a synergistic effect of Ce(III)/Ce(IV) redox centre in ORR and Co activity in OER along with O vacancies providing adsorption sites. We have studied the structural changes associated with the doping by Rietveld refinement of the XRD patterns and correlated the structure to bifunctional oxygen electrocatalytic activity which is found to enhance on increasing the Co and Ce content.

Synergistic electronic coupling/cross-talk between the isolated metal halide units of zero dimensional heterometallic (Sb, Mn) halide hybrid with enhanced emission - Biswas, Anupam; Bakthavatsalam, Rangarajan; Das, Deep K.; Sam, Jisvin; Mali, Bhupendra P.; Biswas, Chinmoy; Maana, Narugopal; Thomson, Stuart; Raavi, Sai Santosh Kumar; Kurungot, Sreekumar; Gonnade, Rajesh G.; Dutta, Sudipta; et al. (Journal of Materials Chemistry C, 2021)
Heterometallic 0D metal halide hybrids, consisting of more than one kind of metal halide units, are anticipated to manifest synergistic effects on the photo-physical properties of the constituent metal halide units. Such architectures hold great promise for design and development of function-targeted materials. However, heterometallic 0D hybrids, featuring isolated metal halide units, typically do not show any synergistic effects due to large inter-unit spatial separations that inhibit interactions/coupling between the constituent metal halide units. It remains challenging to design synthetic strategies that would support structural modifications to allow synergistic electronic coupling between the metal halide units in heterometallic 0D hybrids. Here, we report synthesis and characterization of heterometallic (Sb, Mn) 0D hybrid, namely Tris SbMnCl, with isolated MnCl5 units, (Sb/Mn)Cl-6 units, dispersed in the organic ligand matrix and layer of dynamic and networked water molecules. Steady state and time resolved emission spectra (TRES) analysis suggests strong synergistic interaction between the isolated metal halide units. Efficient energy transfer from the strongly absorbing Sb centres to emissive Mn centres results in the observed enhanced emission. Proton conductivity measurements together with first-principles calculations suggest the unique role of the networked water molecules in mediating the electronic coupling/energy transfer between the separated metal halide units in Tris SbMnCl hybrid. This report highlights the role of structure/composition of the synthesized heterometallic 0D hybrid in attaining electronic dimensionality higher than 0D through synergistic electronic interaction between the isolated metal halide units.

Single-step synthesis of exfoliated Ti3C2Tx MXene through NaBF4/HCl etching as electrode material for asymmetric supercapacitor - Ghosh, Meena; Szunerits, Sabine; Cao, Ning; Kurungot, Sreekumar; Boukherroub, Rabah (ChemistrySelect, 2022)
Two-dimensional Ti3C2Tx MXene, derived from the parent Ti3AlC2 phase, is considered a promising electrode material for electrochemical energy storage applications. Ti3C2Tx MXene synthesis methods often employ concentrated hydrofluoric acid (HF), which is harsh, corrosive, and hazardous to the environment. Herein, we report the preparation of Ti3C2Tx MXene following a new synthetic route under a mild reaction condition comprising an aqueous solution of NaBF4 and HCl. This etching environment at a moderate temperature of 130 degrees C effectively removes the Al layer of the Ti3AlC2 precursor, assisted by the in situ formed HF in the reaction medium. Electron microscopy images of the as-prepared Ti3C2Tx (MX-130) reveal a partially exfoliated nanosheet-like morphology. The material displays a specific capacitance of 262 F g(-1) (three-electrode assembly, 1 A g(-1), -0.85 to -0.25 V vs. Hg/Hg2SO4) in 1 M H2SO4 electrolyte. The achieved specific capacitance is superior to that of Ti3C2Tx prepared via the common HF-treatment (25 F g(-1)). Additionally, the potential application of the optimized MXene as a negative electrode material is demonstrated in a quasi-solid-state RuO2|MX-130 asymmetric supercapacitor device.
Keywords: asymmetric supercapacitor; Electrochemistry; Fluoride salt etchant; Layered electrode materials; Transition metal carbides

Synthesis of a highly electron-deficient, water-stable, large ionic box: multielectron accumulation and proton conductivity - Shukla, Jyoti; Illathvalappil, Rajith; Kumar, Sharvan; Chorol, Sonam; Pandikassala, Ajmal; Kurungot, Sreekumar; Mukhopadhyay, Pritam (Organic Letters, 2022)
pi-acidic boxes exhibiting electron reservoir and proton conduction are unprecedented because of their instability in water. We present the synthesis of one of the strongest electron-deficient ionic boxes showing e(-) uptake as well as proton conductivity. Two large anions fit in the box to form anion-pi interactions and form infinite anion-solvent wires. The box with NO3-center dot center dot center dot water wires confers high proton conductivity and presents the first example that manifests redox and ionic functionality in an organic electron-deficient macrocycle.

Salicylaldehydate coordinated two-dimensional-conjugated metal-organic frameworks - Mohammed, Abdul Khayum; Pena-Sanchez, Pilar; Pandikassala, Ajmal; Gaber, Safa; AlKhoori, Ayesha A.; Skorjanc, Tina; Polychronopoulou, Kyriaki; Kurungot, Sreekumar; Gandara, Felipe; Shetty, Dinesh (Chemical Communications, 2023)
A novel class of copper-based 2D-c-MOF was synthesized from 1,3,5-triformylphloroglucinol using green mechano-chemistry. Herein, metal coordination with the salicylaldehyde functional moiety was explored for the first time in MOFs. Moreover, an intrinsic semiconductive copper-based SA-MOF thin film was fabricated using an in situ salt-free method at room temperature.

Surface-anchored PtNi alloy network over SiO2 (PtNi/SiO2): a versatile carbon-free cathode for proton exchange membrane fuel cells (PEMFCs) - Kumar, Sachin; Yoyakki, Athira; Kurungot, Sreekumar (ACS Applied Engineering Materials, 2024)
The large-scale commercialization of the PEMFCs is hindered due to the high cost of the Pt-based electrocatalysts (Pt/C) and the low durability associated with the oxidation of the carbon support in Pt/C. Many Pt-based carbon-free electrocatalysts have been explored, exhibiting excellent stability and activity, but the performance is further expected to be improved by developing suitable Pt alloy catalysts based on the carbon-free supports. To explore this possibility, we have developed a PtNi/SiO2 alloy system, which acts as a carbon-free electrocatalyst exhibiting enhanced activity for the oxygen reduction reaction (ORR). A half-cell study of PtNi/SiO2 (45 wt%) shows ∼4.3 times higher ORR activity compared to the state-of-the-art Pt/C (40%). The uniform distribution of the PtNi nanoparticles over SiO2 is the crucial feature of the catalyst. PtNi/SiO2 shows better durability even after 5000 cycles compared to the state-of-the-art Pt/C. The catalyst shows a negative shift in the half-wave potential (E1/2) by only 5 mV, which is lower than that of the 11 mV drop incurred by Pt/C. Considering this high activity of the PtNi/SiO2 catalyst for the ORR, we tried to explore the possibility of demonstrating a single-cell PEMFC in the MEA by pairing the catalyst as the cathode along with the Pt/C as the anode. This paired configuration of the single cell is found to be providing promising performance by delivering a current density of 960 mA/cm2 at 0.60 V and a maximum power density of 835 mW/cm2. Thus, this study outlines the possibility of developing potential alloy combinations of Pt on carbon-free substrates and then deploying them as electrodes for PEMFC applications. In the context of mitigating the carbon corrosion-related issues without compromising the intrinsic activities of the catalysts, the development of suitable alloy combinations on various carbon-free substrates is of significant technological advantages. The formation of the alloy phase along with the fine and uniform distribution of the alloy nanoparticles on the SiO2 substrate, followed by its successful deployment as the cathode of a single cell, points toward the scope of exploring material developments in this direction.

Self-supported super-hydrophilic interconnected nanospikes and particles of MoS2-Ni3S2/NF with optimum d-band center for anion exchange membrane water electrolyzer - Kumar, Yogesh; Barik, Sidharth; Samudre, Nikhil S.; Kharabe, Geeta Pandurang; Chauhan, Inderjeet; Manna, Narugopal; Bhat, Suresh; Kurungot, Sreekumar (Advanced Sustainable Systems, 2025)
There is an imperative need for highly efficient electrocatalysts for cost-effective hydrogen production. Herein, a self-supported, hybrid composite as a bifunctional electrocatalyst is introduced. This is achieved by in situ growth of MoS2-Ni3S2 on nickel foam (NF), designated as MoS2-Ni3S2/NF, synthesized by a facile one-step hydrothermal synthesis method. MoS2-Ni3S2/NF exhibits low overpotentials of only 187 and 146 mV for OER and HER, respectively, to achieve a current density of 10 mA cm-2 in 1 M KOH. The practical application of the designed bifunctional electrocatalyst is verified by constructing the MoS2-Ni3S2/NF || MoS2-Ni3S2/NF symmetrical membrane electrode assembly (MEA) of 4 cm2 working area for the anion exchange membrane water electrolyzer. The system shows continuous electrolysis for the monitored 48 h duration. For OER, an optimum d-band center of -1.66 eV for the heterostructure is calculated from the Density Functional Theory (DFT) studies. The factors like the unique structure of the electrocatalyst, enhanced hydrophilicity, improved electrochemically accessible number of sites (ECASs), and optimum d-band center, are expected to be the primary contributors to the system's improved performance. Thus, the present finding unveils a straightforward synthesis approach for creating a stable electrocatalyst for advancing commercial water electrolysis in the realm of renewable electrochemical energy conversion.
Keywords: AEM; d-band center; electrolyzer; HER; OER

Self-healing hydrogel electrolyte enabled by dynamic polar covalent and noncovalent interactions for high-performance rechargeable zinc-metal batteries: a leap toward sustainable energy storage - Puthiyaveetil, Priyanka Pandinhare; Kurian, Rachna Maria; Samudre, Nikhil S.; Balasubramanian, Rajalakshmi; Torris, Arun; Pockil, Fayis Kanheeram; Bhat, Suresh; Ajithkumar, T. G.; Krishnamurty, Sailaja; Kurungot, Sreekumar (Advanced Energy Materials, 2026)
Hydrogel polymer electrolytes with superior multifunctional properties are promising alternatives to aqueous electrolytes for resolving interfacial issues in rechargeable zinc-metal batteries. In this study, an intrinsic self-healing hydrogel polymer electrolyte (PHBC-4) is synthesized, engineered through an integrated approach involving the polar covalent (B & horbar;O bond), hydrogen-bond (polyvinyl alcohol-hydroxypropyl methylcellulose interface), and coordination-type (Zn & horbar;O) interactions to enable self-healing functionality. The PHBC-4 has demonstrated high ionic conductivity (4.6 x 10-2 S cm-1), good oxidative stability (2.3 V vs Zn|Zn2+), a high cation transference number (0.89), superior tensile strength (0.32 MPa), and an impressive healing efficiency of 93% achieved just within 5 min, confirming its robust self-healing capability. In Zn||Zn symmetric cells, it effectively suppresses dendrite growth, ensuring stable cycling for over 1032 h with an areal capacity of 1.0 mAh cm-2 at a current density of 1.0 mA cm-2. When paired with a Zn-doped MnO cathode in the rechargeable homemade pouch cell, the system delivers a high specific capacity of 160 mAh g-1 at 0.10 A g-1 and cycling stability up to 493 charge-discharge cycles at 2.0 A g-1. The self-healing ability of PHBC-4 HGPE is confirmed in a homemade pouch cell via OCV and charge-discharge tests, demonstrating stable performance. The DFT studies confirm molecular-level interactions within the hydrogel heterostructure.
Keywords: dendrite inhibition; flexible rechargeable zinc metal battery; high cation transference number; self-healing hydrogel polymer electrolyte